Adverse Events of Injectable Deoxycholic Acid. Issue 7 (July 2020) - Pham, Christine T.; Lee, Alfred; Sung, Calvin T.; Choi, Franchesca; Juhasz, Margit; Mesinkovska, Natasha A.
Abstract : BACKGROUND: Injectable deoxycholic acid (DCA) may be used to remove excess submental fat and off-label for local adipose reduction. Despite DCA's widespread use, rare incidences of severe, systemic, long-term adverse events (AEs) have been reported. OBJECTIVE: To evaluate the potential side effects associated with injectable DCA. METHODS AND MATERIALS: A systematic review was conducted using PubMed, Cochrane, CINAHL, and Web of Science using PRISMA guidelines to gather the literature relating to DCA or deoxycholate-associated AEs and their management. RESULTS: Twenty-eight manuscripts were included after full article review. Most commonly, patients experienced mild localized AEs, whereas a small number of patients experienced severe pain, alopecia, nasopharyngitis, dysphagia, dizziness/lightheadedness, and gastrointestinal upset. Severe, long-term AEs were reported as rare in the evaluated literature. Deoxycholic acid injections in large volumes were more likely to cause severe adverse effects. CONCLUSION: Self-resolving, mild side effects and severe but rare adverse effects have been reported with DCA use making it a safe treatment for local adipose reduction. Further studies are necessary to determine its safety profile, especially when using DCA in off-label areas.